2019
DOI: 10.1038/s41598-019-43776-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of the triglyceride (triacylglycerol) glucose index in the development of cardiovascular events: a retrospective cohort analysis

Abstract: This study aimed to evaluate the role of the triglyceride (triacylglycerol) glucose (TyG) index in predicting and mediating the development of cardiovascular disease (CVD). This cohort study included 6078 participants aged over 60 years who participated in a routine health check-up programme from 2011 to 2017. The competing risk model, cox regression model and multimediator analyses were performed. TyG was calculated as ln [fasting triglyceride (mg/dl) × fasting plasma glucose (mg/dl)/2]. During a median 6 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
138
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(150 citation statements)
references
References 45 publications
6
138
3
1
Order By: Relevance
“…A population-based, prospective cohort study including 5014 apparently healthy subjects demonstrated that a higher TyG index was associated with an increased risk of incident CVD (CHD, PAD and CVA), independent of diabetic status [12]. Similarly, another population-based but retrospective cohort study including 6078 apparently healthy subjects over 60 years old also demonstrated that an elevated TyG index was significantly associated with an increased risk of developing CVD events, including both fatal and non-fatal CHD and CVA, independent of diabetic status [13]. Alizargar et al showed that the TyG index was significantly correlated with the total amount of carotid plaque and the intima-media thicknesses of the internal, external, and common carotid arteries in hypertensive and normotensive community-dwelling individuals [14].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…A population-based, prospective cohort study including 5014 apparently healthy subjects demonstrated that a higher TyG index was associated with an increased risk of incident CVD (CHD, PAD and CVA), independent of diabetic status [12]. Similarly, another population-based but retrospective cohort study including 6078 apparently healthy subjects over 60 years old also demonstrated that an elevated TyG index was significantly associated with an increased risk of developing CVD events, including both fatal and non-fatal CHD and CVA, independent of diabetic status [13]. Alizargar et al showed that the TyG index was significantly correlated with the total amount of carotid plaque and the intima-media thicknesses of the internal, external, and common carotid arteries in hypertensive and normotensive community-dwelling individuals [14].…”
Section: Discussionmentioning
confidence: 89%
“…Numerous clinical studies have indicated that the TyG index is associated with CVD morbidity and mortality in the general population and many patient cohorts including both non-diabetic and diabetic patients [12][13][14][15][16][17][18][19][20]; however, no previous study has exclusively investigated the prognostic usefulness of the TyG index for CV events after PCI in patients with T2DM and ACS. Therefore, we examined the relationship between the baseline TyG index and adverse CV outcomes in patients with T2DM and ACS who underwent PCI.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent data suggest that TyG index could provide significant prognostic information in patients with established CAD [16][17][18][19]. In fact, TyG index is associated with not only the incidence of cardiovascular disease (CVD) but also the development of type 2 diabetes [20][21][22][23][24][25]. All these suggest that it is may be plausible to use the TyG index as a predictor for future cardiovascular risk in patients with diabetes and CAD.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that IR evaluated by TyG index is strongly related to the incidence of diabetes and prediabetic status, suggesting that TyG index may be a considerable predictor for early identifying individuals at high risk of developing diabetes and prediabetes, even performs better than other risk factors such as FBG and weight gain [14-16, 37, 38]. Studies also showed that elevated level of TyG index is prominently associated with an increased risk of developing cardiovascular disease including CAD and ischemic stroke, which suggests evaluation of TyG index might be helpful for identifying people who is susceptible to cardiovascular disease, despite existence of traditional cardiovascular risk factors or not [17,18,[39][40][41]. And for patients with stable CAD, TyG index has been demonstrated to be positively related to future adverse clinical outcomes, indicating that TyG index may play an important role in the prediction of clinical prognosis in patients with stable CAD [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that an increased level of TyG index is closely related to higher incidence of diabetes and prediabetic status [14][15][16]. Furthermore, the association between TyG index and the prevalence and prognosis of cardiovascular disease has been con rmed by certain clinical researches, despite the existence of diabetes or not at baseline [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%